STUDENTS’ WRITING ACHIEVEMENTS IN USING PAST TENSE ON NURSING STUDENTS OF STIK BINA HUSADA - Arief Pamuji (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2023)
Writing activity is an activity that is often carried out by many people, such as students. They often write both formally and informally. The objective of this research was to find out The students’ writing achievements in using past tense on nursing students of STIK Bina Husada. The sample of this research was taken by using totaling sampling technique with 30 nursing students of the fifth semester. The data was obtained based on observation of students’ writing in using past tense in every meeting from the October 3rd to 4th November 2022. Then from the data analysis, it was obtained that there was a good progress on students’ writing where t response by writing English related to the material since the first day to the fifth day. For the first day the average score of students’ writing was 50 in their writing result and in the the fifth day the average score for students’ writing was 70. Since this research focused on students’ tenses in writing, it showed that the students had good progress from fair category 3.80 (76%) to good category 4.97 (99.33%). It could be concluded that it the students were able to use past tense in their writing.